Impact of Public Capital Expenditure on Economy Growth of Nigeria - Joy, Jideofor Nnennaya; Okafor, Michah Chukwuemeka; Nmesirionye, Josephine Adanma (Journal of Asian Multicultural Research for Economy and Management Study, 2021)
The research investigates the relationship between governmental capital spending and economic development in Nigeria. Several issues of the Central Bank of Nigeria's statistics bulletin were used in the research, which yielded a large amount of data. The data was submitted to a unit root test, which was performed using the Augmented Dickey fuller (ADF) method, in order to determine its time series characteristics. The variables' socioeconomic characteristics were obtained via the use of descriptive statistics. Because of the varying order of integration seen in the unit root, cointegration and regression analysis were carried out utilizing the ARDL- Autoregressive Distributed Lag method, which is an acronym for Autoregressive Distributed Lag. The results show that public capital investment has a negative and statistically significant (tcal = -2.6996) impact on the Nigerian economy, as assessed by the GDP growth rate, according to the data. The results demonstrate that when capital expenditures in Nigeria get the attention they deserve, they have the potential to contribute to economic development in the country. This research recommends that the government manage capital spending in an appropriate manner in order to enhance the nation's productive capacity and accelerate economic development in light of the results.